Analisis Determinan Prevalensi Ketidakcukupan Konsumsi Pangan Di Indonesia - Rani Susanti; Irfan, Muhammad (Universitas Negeri Padang, 2024)
Food security is one of the priorities in national development efforts. The ultimate goal is to end hunger and malnutrition by 2030, which is a goal of the Sustainable Development Goals (SDGs). Achieving this goal requires a sustainable food production system that implements resilient agricultural practices. One of the indicators in assessing food security is the prevalence of Undernourishment. This study aims to analyze and determine the effect of Economic Growth, Poverty, Rice Production, Rainfall, and Temperature on the Prevalence of Undernourishmnet in Indonesia. This study uses panel data from 2018 to 2022. This study uses an equation model using the Random Effect Model (REM). The results of this study indicate that rice production and rainfall have a significant effect on the prevalence of Undernourishment, while the variables of economic growth, poverty, and temperature have no significant effect on the prevalence of inadequate food consumption. The influence of these variables is expected to encourage the improvement of national food security.